Knowledge and Awareness Regarding Clinical Management of Thin Ridges Among Dentist Practicing Dental Implants - A Questionnaire Based Online Survey - JEBARAJ, SAM; R, DR. SUBHASHREE (The journal of contemporary issues in business and government, 2020)
The study aims to assess the knowledge and awareness regarding clinical management of thin ridges among dentists practising dental implants. Deficient alveolar ridge is a common difficulty faced by dental practitioners during replacement of missing teeth by dental implants. Hence there is a need to gain adequate bone to place implants. There are various methods to manage thin ridges. Proper knowledge and skills are needed to manage this situation. This study was designed around a questionnaire assessing the knowledge and awareness among dentists on an online platform - google forms was used to prepare the survey, the link of the survey was distributed to the volunteers using convenience sampling and snowball sampling methods. The data was collected, tabulated in excel sheets, and analyzed using the SPSS software. In this study most of the Prosthodontist, Oral Surgeon and Periodontist feel that managing reduced height is challenging and most of the specialists prefer bone expansion than ridge splitting. The commonly used graft material was autograft and the specialist preferred to augment bone when encountered a thin ridge.